Soil pH periodic assortment with smart irrigation using aerial triboelectric nanogenerator - Dhandapani Karthikeyan; Deeba Kannan; Brindha Gunasekaran; Hemalatha Selvaraj; Saurabh Gupta; Ravindran Ramkumar; Krishnasamy Vijayakumar (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The paper presents an idea on pre-emptively ascertaining the soil pH value on an agriculture field amalgaming drone for aerial photo and subsequent smart irrigation model with the help of internet of things (IoT). The drone used for the aerial footage (multispectral imaging) consists of specialized cameras with filters that would help in ascertaining vegetation and health of the crops in the agriculture land. The IoT device used in smart irrigation model consists of sensors which accumulate data and execute the commands given in a recurring fashion of delay. Moreover, the use of triboelectric nanogenerator (TENG) would help in feasible energy harvesting for agricultural land use.